Comparison of Diagnostic Performance of Spread Through Airspaces of Lung Adenocarcinoma Based on Morphological Analysis and Perinodular and Intranodular Radiomic Features on Chest CT Images - Qi, Lin; Li, Xiaohu; He, Linyang; Cheng, Guohua; Cai, Yongjun; Xue, Ke; Li, Ming (Frontiers in Oncology, 2021)
Object: STAS is associated with poor differentiation, KRAS mutation and poor recurrence-free survival. The aims of this study are to evaluate the ability of intra- and perinodular radiomic features to distinguish STAS at noncontrast CT. Methods: This retrospective study included 216 patients with pathologically confirmed lung adenocarcinoma (STAS+, n = 56; STAS- , n=160). Texture-based features were extracted from intra- and perinodular regions of 2 mm, 4 mm, 6 mm, 8 mm, 10 mm , and 20 mm distances from the tumor edge using an erosion and expansion algorithm. Traditional radiologic features were also analyzed including size, consolidation tumor ratio (CTR), density, shape, vascular change, cystic airspaces, tumor-lung interface, lobulation, spiculation, and satellites sign. Nine radiomic models were established by using the 8 separate models and a total of the 8 VOIs (8-VOI model). Then the prediction efficiencies of the nine radiomic models were compared to predict STAS of lung adenocarcinomas. Results: Among the traditional radiologic features, CTR, unclear tumor-lung interface, and satellite sign were found to be associated with STAS significantly, and the AUCs were 0.796, 0.677, and 0.606, respectively. Radiomic model of combined tumor bodies and all the distances of perinodular areas (8-VOI model) had better predictive efficiency for predicting STAS+ lung adenocarcinoma. The AUCs of the 8-VOI momdel were in the training and verification sets were 0.907 (95%CI, 0.862-0.947) in the training set, and 0.897 (95%CI, 0.784-0.985) in the testing set, and 0.909 (95%CI, 0.863-0.949) in the external validation set, and the diagnostic accuracy in the external validation set was 0.849. Conclusion: Radiomic features from intra- and perinodular regions of nodules can best distinguish STAS of lung adenocarcinoma.